Munda Make Over Series One, AICCRA Zambia - Smith, Georgina (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The first series of Munda Make Over disseminated information on climate change adaptation, farming as a business, financial inclusion, and improved livelihoods to 654,751 people in Zambia. The information was disseminated on national television between December 2022 and June 2023. On average, three people watched the show together, and it is estimated that around 1.9 million people had access to the Munda Make Over climate information. Of these, 31% were farmers with access to TV. The series were supported by the AICCRA, Ukama Ustawi and ClimBer project partners.